Systematic Literatur Review (SLR): Peran Pemecahan Masalah pada Kurikulum Matematika Tahap Kunci 1 dan 2 di Inggris - Suyanto Suyanto; Iwan Junaidi; Mulyono Mulyono (Journal on Education, 2024)
The purpose of this study is to describe the application of problem solving in the mathematics curriculum in England in 2013 key stages 1 and 2. This research uses a Systematic Literature Review (SLR) approach to the role of problem solving in curriculum, learning, and evaluation. The results of the study obtained (1) the integration of problem solving development in the mathematics curriculum in England in 2013 key stages 1 and 2, students become fluent in the basics of mathematics, reason systematically and can solve problems by applying their mathematics to a variety of routine and non-routine problems including breaking down problems into a series of simpler steps and persistently looking for solutions; (2) in the learning of mathematics problem solving key stages 1 and 2 in the form of, teachers teaching for problem solving, teaching about problem solving, and teaching through problem solving (3) in the evaluation of mathematics learning in the form of formative, summative, and portfolio assessments.